Effects of auricular stimulation on weight- and obesity-related parameters: a systematic review and meta-analysis of randomized controlled clinical trials - Hua, Kevin; Usichenko, Taras; Cummings, Mike; Bernatik, Miriam; Willich, Stefan N.; Brinkhaus, Benno; Dietzel, Joanna (Frontiers in Neuroscience, 2024)
The number of randomized controlled trials using stimulation of auricular vagal sensory nerves by the means of electrical stimulation, auricular acupuncture or acupressure to support weight loss has increased markedly over the last three decades. This systematic review focuses on effects of auricular stimulation on the anthropometric parameters and obesity related blood chemistry.The following databases were searched until November 2021: MEDLINE (PubMed), EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), ISI Web of Science, and Scopus Database. Data collection and analysis was conducted by two reviewers independently. Quality and risk assessment of included studies was performed using the risk of bias tool of the Cochrane Handbook and the meta-analysis of the effect of the most frequently assessed biomarkers was conducted using the statistical software RevMan.Results: Full texts of 1274 studies were screened, 22 contained data on obesity related outcomes, 15 trials with 1333 patients were included in the meta-analysis. The overall quality of the included trials was moderate. Auricular stimulationS(AS) significantly reduced BMI (mean difference (MD) = -0.38 BMI-points, 95% CI (-0.55 to -0.22), p<0.0001), weight (MD = -0.66 kg, 95% CI (-1.12 to -0.20), p=0.005), waist-circumference (MD = -1.44cm, 95% CI (-2.69 to -0.20), p=0.02) and the hormones leptin, insulin as well as the HOMA insulin resistance compared to controls. No significant reduction of body fat was found in body fat, hip circumference, ratio of waist/hip circumference, cholesterol, LDL, triglycerides, adiponectin, ghrelin, and glucose levels. The AS was safe throughout the trials, with only minor adverse reactions.The study results suggest that a reduction of weight and BMI can be achieved by AS in obese patients, however the size of the effect does not appear to be of clinical relevance.Effects might be underestimated due to active sham trials.